(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article focuses on the semіоtic, linguistic and cultural identification of B. D. Hrynchenko’s aphorisms in the context of new approaches in linguistic studies – linguaculturological, pragmalinguistic and anthropological. The article also deals with the theoretical and practical aspects of aphorisms in the paremiological conception and gives additional information on the main approaches in the linguistic identification of these units. The article generalizes the complex of linguistic phenomena that are in the basis of structural modelling of aphorisms, researches the connections in their meanings, stylistic peculiarities and pragmatic direction in the idiolect of B. D. Hrynchenko.